Managed decline? Muddling through with the sterling (dis)agreements, 1968-74 - Alan De Bromhead; David P. Jordan; Francis Kennedy; Jack Seddon (Queen's University Centre for Economic History (QUCEH), 2023)
How do policy makers manage the decline of an international currency? This paper examines British policy towards the pound sterling's international role in the years 1968-74. Using previously uncited government archival sources, we revisit the view that the 'sterling agreements' of 1968-74, bilateral contracts made between the UK and governments holding sterling, formed a successful paradigm shift in British policy, towards deliberately managing sterling's international 'retirement'. Our research indicates that there was no settled consensus or strategic direction to British policy in this period, a case of 'muddling through'. Indeed, when feasible options presented themselves, British officials sought to maximise, not reduce, international sterling holdings.
Keywords: N10; F02; F22; F33; 330; Sterling Area Agreements; international currency; sterling policy; disintegration